SECONDARY TRAUMATIC FACTORS IN PATIENTS WITH DIFFUSE LESIONS OF THE BRAIN TISSUE IN JOINT HEAD INJURIES. - Isakov B.M.; Mirzeyuldashev N.N; Isakov K.B. (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
now there is a constant growth rate of injury in all countries of the world. As a result of all the injuries that have arisen, the disability of the axiom, the central nervous system injuries among the causes leading to the death cases are in the first place (30-40%), and the mortality cases are lagging behind the indicators of cardiovascular and oncological diseases with much observation among the most active layer of axioms (18-45 years).